MODEL LOTRE ; STRATEGI PENETUAN SEWA BENGKOK DESA (Studi Fenomenologi Pada Desa Tawangrejo Kec. Wonodadi Kab. Blitar) - Diana Elvianita (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2016)
This Research aims to determine how the determination of“Bengkok-- land leases used Tawangrejo Rural District of WonodadiBlitar? The method used is qualitative with phenomenologicalapproach. The results of this research The village governmentTawangrejo Wonodadi District of Blitar Using “Lotre Model-- todetermine a “Bengkok-- land tenants as the principle of justice andequity. this method intended for residents of the village can bealternately each year to hire a “Bengkok-- land and residents can feelthe results of the village land